Mirror As Inspiration In The Creation Of Artworks - Kerine Claudya Wijaya; Ariesa Pandanwangi; Belinda Sukapura Dewi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Every artist has the goal of creating works of art that cannot be separated from the spiritual feelings experienced daily. The creative process of creating this work of art is initiated from the mirror which will be explored in the work of art. The method used is descriptive qualitative study and experimental method. The problem in this creation process is how the phenomenon that occurs when humans feel unhappy in their inner life so that they feel depressed, even judged between individuals, both physically and non-physically. The result of this creation process is a puzzle arrangement which is a metaphor for the results of reflection as well as the spiritual relationship of the soul with the body that has been experienced in living and contemplating life. The message conveyed through this work is that humans must understand each other.Setiap seniman memiliki tujuan menciptakan karya seni yang tidak lepas dari perasaan spiritual yang dialami sehari-hari. Proses kreatif penciptaan karya seni ini digagas dari cermin yang akan dieksplorasikan pada karya seni. Metode yang dipergunakan adalah studi metode deskriptif kualitatif dan metode eksperimental. Permasalahan dalam proses penciptaan ini bagaimana fenomena yang terjadi ketika manusia merasakan perasaan tidak bahagia dalam kehidupan batinnya sehingga merasa tertekan, bahkan dinilai antar individu, baik secara fisik maupun non fisik. Hasil dari proses penciptaan ini adalah susunan puzzle yang merupakan metafora dari dari hasil refleksi sebagaimana hubungan spiritual jiwa dengan tubuh yang telah berpengalaman dalam penjalanan hidup dan perenungan hidup. Pesan yang disampaikan melalui karya ini adalah manusia harus saling memahami antara satu dengan lainnya